Single domain antibody-scFv conjugate targeting amyloid β and TfR penetrates the blood–brain barrier and interacts with amyloid β - Rebecca Faresjö; Elisabet O. Sjöström; Tiffany Dallas; Magnus M. Berglund; Jonas Eriksson; Dag Sehlin; Stina Syvänen (mAbs)
Neurodegenerative diseases such as Alzheimer’s disease (AD) pose substantial challenges to patients and health-care systems, particularly in countries with aging populations. Immunotherapies, including the marketed antibodies lecanemab (Leqembi®) and donanemab (KisunlaTM), offer promise but face hurdles due to limited delivery across the blood–brain barrier (BBB). This limitation necessitates high doses, resulting in increased costs and a higher risk of side effects. This study explores transferrin receptor (TfR)-binding camelid single-domain antibodies (VHHs) for facilitated brain delivery. We developed and evaluated fusion proteins (FPs) combining VHHs with human IgG Fc domains or single-chain variable fragments (scFvs) of the anti-amyloid-beta (Aβ) antibody 3D6. In vitro assessments showed varying affinities of the FPs for TfR. In vivo evaluations indicated that specific VHH-Fc and VHH-scFv fusions reached significant brain concentrations, emphasizing the importance of optimal TfR binding affinities. The VHH-scFv fusions were further investigated in mouse models with Aβ pathology, showing higher retention compared to wild-type mice without Aβ pathology. Our findings suggest that these novel VHH-based FPs hold potential for therapeutic and diagnostic applications in AD, providing a strategy to overcome BBB limitations and enhance brain targeting of antibody-based treatments. Furthermore, our results suggest that a given bispecific TfR-binding fusion format has a window of “optimal” affinity where parenchymal delivery is adequate, while blood pharmacokinetics aligns with the desired application of the fusion protein.